(untitled) (European Journal of Pure and Applied Mathematics, 2022)
This paper aims to apply the concept of rough sets to Pythagorean fuzzy sets in UP-algebras. Then we introduce fifteen types of rough Pythagorean fuzzy sets in UP-algebras and study their generalization. In addition, we will also discuss t-level subsets of rough Pythagorean fuzzy sets in UP-algebras to study the relationships between rough Pythagorean fuzzy sets and rough sets in UP-algebras.